Resource mobilisation: a prerequisite for project implementation, success and sustainability - Molefe, Chedza (My University, 2012)
Unprecedented developments in technology that lead to remarkable increases in knowledge processing and production, coupled with new user demands, have made digitization essential. Access to resources has dwindled in the wake of the economic slow-down. It has become imperative to make projects attractive to donors through proper and elaborate planning. Collaboration, an old concept in libraries, is one strategy for attraction. Resource mobilization, an important part of planning, should always be the first step in embarking on digitization projects. It should therefore be carried out in a systematic way following a resource mobilization strategy with specific steps. The Organization of African Unity (OAU) now defunct project illustrates how deficiencies in resource mobilization can lead to project failure. It is proposed that ICADLA set up a steering team to work with Economic Commission for Africa (ECA) and the African Union Commission (AUC) to implement resource mobilization strategy with the view to coordinating and promoting digitization projects in Africa for the development of an African Digital Library of information for development.
Keywords: Project management; Resource allocation; Digital libraries